THE ANALYSIS OF WORD FORMATION PROSESS FROM FOOTBALL ENTHUSIASTS ON SOSIAL MEDIA - Kamal, Shofia; Afifah, Alif Jihan; Laudzai, Ahmad Rashif; Burhanuddin, Darmawati (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The aim of this study is for analysing the kinds of word formation process which football enthusiasts use specifically on their social media as well as of investigate the most used word formation process. Then, the research design of this article is qualitative study. Documentation technique was used as the instrument. The conclusion is concluded that the most used formations process on Instagram was initialisms. Then on Twitter there were initialism, clipping and also conversion. Otherwise, compounding was mostly used by Facebook users. Thus, researcher in the future can analyse word formation process that are used by other kinds of enthusiasts both on social media or mass media .